Local labor markets in Canada and the United States - David Albouy; Alex Chernoff; Chandler Lutz; Casey Warman (Bank of Canada, 2019)
We examine local labor markets in the United States and Canada from 1990 to 2011 using comparable household and business data. Wage levels and inequality rise with city population in both countries, albeit less in Canada. Neither country saw wage levels converge despite contrasting migration patterns from/to high-wage areas. Local labor demand shifts raise nominal wages similarly, although in Canada they attract immigrant and highly skilled workers more, while raising housing costs less. Chinese import competition had a weaker negative impact on manufacturing employment in Canada. These results are consistent with Canada's more redistributive transfer system and larger, moreeducated immigrant workforce.
Keywords: J21; J31; J61; R12; N32; 330; Labour markets